Odpowiedź :
Odpowiedź:
~ - mniej więcej równa się
5√3 + 2 ~ 5 * 1,73 +2 ~ 8,66 + 2 ~ 10,66
7√2 ~ 7 * 1,41 ~ 9,89
z tego wynika że:
7√2 < 5√3 + 2
Odpowiedź:
a = 5[tex]\sqrt{3}[/tex]+2
b = 7[tex]\sqrt{2}[/tex]
[tex]a^{2}[/tex] = 25*3 + 20[tex]\sqrt{3}[/tex] + 4 = 79 + 20[tex]\sqrt{3}[/tex]
[tex]b^{2}[/tex] = 49*2 = 98
ponieważ
[tex]\sqrt{4}[/tex] = 2
[tex]\sqrt{1}[/tex] = 1
[tex]\sqrt{4}[/tex] > [tex]\sqrt{3}[/tex] > [tex]\sqrt{2}[/tex] > [tex]\sqrt{1}[/tex]
2 > [tex]\sqrt{3}[/tex] > 1 to mamy
[tex]a^{2}[/tex] = 79 + 20[tex]\sqrt{3}[/tex] > 99
[tex]b^{2}[/tex] = 98
czyli:
[tex]a^{2}[/tex] = 79 + 20[tex]\sqrt{3}[/tex] > 99 > 98 = [tex]b^{2}[/tex]
dlatego
[tex]a^{2}[/tex] > [tex]b^{2}[/tex]
więc
a > b
5[tex]\sqrt{3}[/tex]+2 > 7[tex]\sqrt{2}[/tex]
Szczegółowe wyjaśnienie:
[tex](a+b)^{2}[/tex] = [tex]a^{2}[/tex] + [tex]2ab[/tex] + [tex]b^{2}[/tex]